(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
In Pereyaslav-Khmelnytskiy and its outskirts (Kyiv region, Ukraine), 66 species of bryophytes were found. Among them, three species (Aulacomnium androgynum(Hedw.) Schwägr., Bryum violaceumCrundw. et Nyh.and Orthotrichum diaphanumSchrad. ex Brid.) have not been previously reported for the Left-Bank Forest-Steppe of Ukraine, whilst another three (Dicranum tauricumSapjegin, Sciuro-hypnum reflexum(Starke) Ignatov et Huttunem and Orthotrichum striatumHedw.) are appeared to be rare for this territory. In general, the town’s bryophyte flora consists of forest species and relatively less of weedy taxa.